What shapes EMI students’ achievement goals? The influence of locus of control, future time perspective, and self-regulated learning - Guan, Yuan; Ahmad, Rosliza Binti; Faudzi, Farah Nadia Binti Mohd (Edelweiss Applied Science and Technology, 2025)
This study investigates the factors influencing academic achievement among students enrolled in English as a Medium of Instruction (EMI) programs in Chinese universities, highlighting how motivational orientations, time perspectives, and control beliefs shape learning outcomes. Grounded in Achievement Goal Theory, Future Time Perspective (FTP), and Locus of Control (LOC), the study collected survey data from 480 undergraduate students in accounting and tourism majors. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the measurement and structural models. Results indicate that mastery-approach goals, performance-approach goals, and future time perspective significantly predict academic achievement. Moreover, internal locus of control moderates the relationship between motivational constructs and performance, underscoring its importance in the EMI context. By integrating motivation, time perspective, and control belief theories, this study provides a comprehensive framework to explain academic outcomes in EMI higher education. The findings offer actionable insights for designing instructional strategies and support systems that enhance EMI students’ motivation, self-regulation, and achievement.